2019
DOI: 10.31803/tg-20190215200430
|View full text |Cite
|
Sign up to set email alerts
|

Internet of things and smart warehouses as the future of logistics

Abstract: Innovations and market changes in warehouse and logistics systems force the adaptation and transformation of the existing business model into a business model based on modern technology. With the development of the Internet, RFID (radio-frequency identification) technology and sensors, new innovations are being created that allow the improvement of the existing mode of activity. Implementation of the new technology brings along a number of challenges that organizations must find an adequate response to. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 20 publications
0
23
0
4
Order By: Relevance
“…[680,[688][689][690] WCOA: warehouse and yard management system (IoTcontrolled safe area), inventory management. [677,691] COP: IoT-based safety interaction mechanisms for storage and picking. [678,680] LAFM: condition-based maintenance of equipment (fleet management).…”
Section: Convergence Of Disruptive Technologies In Logisticsmentioning
confidence: 99%
“…[680,[688][689][690] WCOA: warehouse and yard management system (IoTcontrolled safe area), inventory management. [677,691] COP: IoT-based safety interaction mechanisms for storage and picking. [678,680] LAFM: condition-based maintenance of equipment (fleet management).…”
Section: Convergence Of Disruptive Technologies In Logisticsmentioning
confidence: 99%
“…Thus, make warehouse more efficient, reduce costs and increase the quality of materials. [20,21,22] confirmed that applying IoT in inventory, warehousing operations and logistics has a major and a great impact on the warehouse. It help in aking warehouse more efficient as it help in tracking and managing information of the warehouse, tracing everything in it, reducing manpower, increasing the efficiency of warehouse operations, reducing costs and improving the performance of the organization.…”
Section: How Information Sharing and The Use Of Iot Impact On Demand Forecasting And Supply Chainmentioning
confidence: 83%
“…The use of Internet of Things allows to control all activities and goods in the warehouse. The benefits of implementing it in the warehouse translate into the entire supply chain (Buntak et al, 2019). Alias et al (2017) also deals with the adaptation of warehouse management systems (WMS) owned by companies to the new requirements related to digitization.…”
Section: Innovations In Warehousingmentioning
confidence: 99%